PERANAN BAURAN PEMASARAN JASA PENDIDIKAN TERHADAP UPAYA MENINGKATKAN EKUITAS MEREK BERBASIS PELANGGAN PERGURUAN TINGGI (STUDI PADA PERGURUAN TINGGI DI JAWA BARAT) - Dirgantari, Puspo Dewi (Universitas Pendidikan Indonesia, 2016)
West Java province dominates the growth rate of universities in Indonesia, but the number of college students has decreasing. Similarly, the people's preference for universities in West Java as an excellent college and the best universities in Indonesia is still low. These problems show that customer based brand equity of colleges in West Java is not optimal. This study conducted in 2013-2014 and uses a management science approach of marketing. The method used in this study is descriptive survey and explanatory survey. The data used primary and secondary data that was collected through questionnaires and documentation. The data analysis used Stuctural Equation Model (SEM). The results of this study revealed that the marketing mix of educational services has a positive influence on the customer based brand equity of higher education in West Java. The dimensions of customer-based brand equity, especially brand performance dimension, should be getting more attention in order to increase performance and the factors are: facilities, meeting the students need, the speed of service, courtesy, and tuition money. This research is part of my dissertation.Â Keywords: Marketing Mix of Education Services; Customer Based Brand Equity.